2013
DOI: 10.1021/mz3006318
|View full text |Cite
|
Sign up to set email alerts
|

Double-Network Strategy Improves Fracture Properties of Chondroitin Sulfate Networks

Abstract: A tough and ductile, ultrathin film, double-network (DN), biopolymer-based hydrogel displaying the yielding phenomenon was synthesized from methacrylated chondroitin sulfate (MCS) and polyacrylamide (PAAm). The DN of MCS/PAAm exhibited a failure stress more than 20 times greater than the single network (SN) of either MCS or PAAm and exhibited yielding stresses over 1500 kPa. In addition, the stress–strain behavior with a yielding region was also seen in a hydrogel of MCS and poly(N,N-dimethyl acrylamide) (PDMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
109
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 102 publications
(112 citation statements)
references
References 22 publications
2
109
1
Order By: Relevance
“…[ 25 ] Thus, the internal fracture process of the fi rst network is considered to be critical for toughness enhancement, because relatively large damage zones formed in the fi rst network allow for more accumulated damage before macroscopic crack propagation occurs throughout whole networks. [ 26,27 ] Double network (DN) hydrogels with two strong asymmetric networks being chemically linked have demonstrated their excellent mechanical properties as the toughest hydrogels, but chemically linked DN gels often exhibit negligible fatigue resistance and poor self-healing property due to the irreversible chain breaks in covalent-linked networks. Here, a new design strategy is proposed and demonstrated to improve both fatigue resistance and self-healing property of DN gels by introducing a ductile, nonsoft gel with strong hydrophobic interactions as the second network.…”
mentioning
confidence: 99%
“…[ 25 ] Thus, the internal fracture process of the fi rst network is considered to be critical for toughness enhancement, because relatively large damage zones formed in the fi rst network allow for more accumulated damage before macroscopic crack propagation occurs throughout whole networks. [ 26,27 ] Double network (DN) hydrogels with two strong asymmetric networks being chemically linked have demonstrated their excellent mechanical properties as the toughest hydrogels, but chemically linked DN gels often exhibit negligible fatigue resistance and poor self-healing property due to the irreversible chain breaks in covalent-linked networks. Here, a new design strategy is proposed and demonstrated to improve both fatigue resistance and self-healing property of DN gels by introducing a ductile, nonsoft gel with strong hydrophobic interactions as the second network.…”
mentioning
confidence: 99%
“…[5][6][7][8][9] Many experimental and theoretical studies have been performed to reveal the toughening mechanism of the DN gels. [10][11][12][13] These studies have revealed that the high toughness of DN gels derives from the internal fracture of the brittle network during deformation, which is observed by yielding, necking, and irreversible softening (the Mullins effect) phenomena upon tensile deformation.…”
mentioning
confidence: 99%
“…The multicomponent structure of this gel allowed changes in the stress response in different deformation modes, as seen in cartilage. 46 In the following subsections, we will introduce the methods that have been used to evaluate the toughness of hydrogels in general. However, in an effort to determine a reliable method for toughness measurement of hydrogels in cartilage regeneration, we will discuss only the methods that can be applied to both hydrogels and cartilage.…”
Section: Fracture Toughness Measurement Of Hydrogelsmentioning
confidence: 99%